2002
DOI: 10.1007/s00270-002-0426-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Common Bile Duct Obstruction by Pancreatic Cancer Using Various Stents: Single-Center Experience

Abstract: The Wallstent is effective for long-term palliation in patients with obstruction caused by pancreatic cancer invading the middle to lower part of the common bile duct. The covered Wallstent can prevent tumor ingrowth, a problem with the uncovered Wallstent. However, it may be necessary to take measures to prevent the migration or clogging of covered Wallstents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
7

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
1
19
0
7
Order By: Relevance
“…[32][33][34][35] It is also believed that the shortening that occurs following placement aids security. 36 The significantly more frequent migration of plastic stents at approximately 10% 17,32,34,37,38 led Johanson et al 17 to analyse various stent characteristics and clinical factors that may contribute to proximal and distal stent migration. They reported that papillary stenosis is the only risk factor clearly associated with distal stent migration.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] It is also believed that the shortening that occurs following placement aids security. 36 The significantly more frequent migration of plastic stents at approximately 10% 17,32,34,37,38 led Johanson et al 17 to analyse various stent characteristics and clinical factors that may contribute to proximal and distal stent migration. They reported that papillary stenosis is the only risk factor clearly associated with distal stent migration.…”
Section: Discussionmentioning
confidence: 99%
“…The migration of self-expandable metal mesh stents occurs less frequently (0-8%); the actual rate is probably <1% because the surrounding tissue grows through the struts, thus fixing them and sometimes even leading to occlusion [4,5,10,21]. After the placement of self-expanding stents mi- gration may occur, due to the shortening during their expansion as was observed in patient 5 [16].…”
Section: Discussionmentioning
confidence: 86%
“…Their migration can lead to symptoms of biliary obstruction if it is apparent at all [4,12,21]. It may be symptomatic with biliary obstruction or often not display any symptoms at all.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Self-expanding metal stent, due to its minimal invasion, low risk of migration and efficient bile drainage, has been widely used for management of malignant obstructive jaundice (MOJ) [1][2][3][4][5][6][7][8][9][10][11] . Although self-expanding metal stent seems to be the first choice in the palliation of MOJ, high rates of stent occlusion, which were mainly caused by tumor ingrowth or overgrowth, usually lead to jaundice recurrence [12,13] .…”
Section: Introductionmentioning
confidence: 99%